From a sailing convey to a docked brewery : elucidating layers of time and adaptability using the SS nomadic as ideal archetype and Robinson dry dock as host - Jekot, Barbara P. (University of Pretoria, 2017)
Mini Dissertation (MInt (Prof))--University of Pretoria, 2016.